An annotated and illustrated catalog of the Peruvian specimens of Cerambycidae (Coleoptera) housed in the Biological Museum at Lund University, Sweden - Juárez-Noé, Gino; Fägerström, Christoffer (Zootaxa, 2024)
The Peruvian specimens of the family Cerambycidae Latreille, 1802 (Coleoptera) housed in the Biological Museum at Lund University in Sweden are cataloged and illustrated. Photographs of dorsal habitus, labels, and complete label data of all the specimens are provided. There are 81 specimens belonging to 38 species, 29 genera, three subfamilies, and 19 tribes. Anisopodus ligneus Bates, 1863 is a new country record. The presence of Aegomorphus nigricans (Lameere, 1884) in Peru is confirmed. Additionally, 22 species represent new regional records. Colobothea Lepeletier & Audinet-Serville, 1825 and Taeniotes Audinet-Serville, 1835 are the genera with the greatest number of species, three species each. A note on the variation of elytral pubescence in Anisopodus prolixus (Erichson, 1847) is provided.